Revealing the impact of job satisfaction on turnover intention through organizational commitment as a mediation - T. Maryati; U. Udin; M. Musoli; I. Wahyuni (International Journal of Human Capital in Urban Management, 2025)
BACKGROUND AND OBJECTIVES: In the context of private school teachers in Indonesia, job satisfaction is considered a key factor in influencing teachers to remain in their positions within organizations. This study aims to examine the impact of job satisfaction on turnover intention with organizational commitment as an intervening variable among private school teachers, specifically at Muhammadiyah schools in Kapanewon Godean, Indonesia.METHODS: The research method employed is a survey, with questionnaires distributed to 274 respondents. Of these, 205 completed questionnaires were successfully collected and analyzed. Data analysis was performed through Structural Equation Modeling utilizing SmartPLS 3.0 software.FINDINGS: The results of the study indicate that job satisfaction has a significant positive effect on organizational commitment (β = 0.649; t-value = 12.705, p < 0.005), which in turn has a significant negative effect on turnover intention (β = -0.473; t-value = 6.674, p < 0.005). Additionally, organizational commitment was found to mediate the relationship between job satisfaction and turnover intention (β = -0.307; t-value = 5.607, p < 0.005). In other words, an increase in job satisfaction not only directly reduces teachers’ intention to leave their jobs but also does so indirectly by enhancing their commitment to the organization.CONCLUSION: This study highlights the importance of job satisfaction and organizational commitment in retaining high-quality teachers at Muhammadiyah schools. By enhancing job satisfaction, these schools can foster stronger organizational commitment, which, in turn, significantly reduces turnover intentions among teachers. These findings suggest that Muhammadiyah schools should prioritize creating supportive work environments that bolster teacher satisfaction and commitment, as this approach is key to sustaining a dedicated and effective teaching workforce.